Melatonin and Its Homologs Induce Immune Responses via Receptors trP47363-trP13076 in Nicotiana benthamiana - Kong, Mengmeng; Sheng, Tao; Liang, Jing; Ali, Qurban; Gu, Qin; Wu, Huijun; Chen, Jian; Liu, Jia; Gao, Xuewen (Frontiers in Plant Science, 2021)
Melatonin (N-acetyl-5-methoxytryptamine), a naturally occurring small molecule, can protect plants against abiotic stress after exogenous treatmenting with it. It is not known if melatonin homologs, such as 5-methoxytryptamine and 5-methoxyindole, that are easy and more cost-effective to synthesize can stimulate the plant immune system in the same manner as melatonin. In the present study, we assessed the biological activity of the melatonin homologs, 5-methoxytryptamin and 5-methoxyindole. The results showed that melatonin and its homologs all induced disease resistance against Phytophthora nicotianae in Nicotiana benthamiana plants. The application of all three compounds also induced stomatal closure and the production of reactive oxygen species. Gene expression analysis indicated that the expression of genes involved in hydrogen peroxide (H2O2), nitric oxide (NO) production, and salicylic acid (SA) biosynthesis was significantly upregulated by all three compounds. Four homologs of the melatonin receptors were identified by blasting search with the phytomelatonin receptor in Arabidopsis. Molecular docking studies were also used to identify four putative melatonin receptors in N. benthamiana. Further experimentation revealed that silencing of the melatonin receptors trP47363 and trP13076 in N. benthamiana compromised the induction of stomatal closure, PR-1a gene expression and SA accumulation by all three compounds. Collectively, our data indicate that the induction of defense responses in N. benthamiana by melatonin, 5-methoxytryptamine, and 5-methoxyindole involves the melatonin receptors trP47363 and trP13076.